4. Since f(x) = 2x - 1, we are looking for h(2x - 1), which is (2x-1)^2 + 1. By tha time you expand this you'll get, 4x^2 - 4x + 2. So that is the answer.
5. f(f(x)) = f(2x - 1) = 2(2x - 1) - 1 = 4x - 3
6. h(g(x)) = h(3x) = (3x)^2 + 1 = 9x^2 + 1
Answer: 2 1/2
Step-by-step explanation: Divide using long division. The whole number portion will be the number of times the denominator of the original fraction divides evenly into the numerator of the original fraction, and the fraction portion of the mixed number will be the remainder of the original fraction division over the denominator of the original fraction. Hope this helps!! PLZ mark me!!!
Answer:
B represents 9. The opposite would be -9
Step-by-step explanation:
The answer is between 12 & 13
Answer:
44664.59503
Step-by-step explanation:
Hello,
In this question, you're asked to find the radical of a number. However in mathematics, the radical of a number simply means "√" and not directly square root of that number, its could be the cube root "³√" or even the fourth root "⁴√".
In this case, we're asked to find the 3 radical of p/q which means 3√(p/q)
P = 2.78×10¹¹
Q = 3.12×10⁻³
p / q = 2.78×10¹¹ / 3.12×10⁻³
p / q = 8.91×10¹³
The 3 radical = 3√(8.91×10¹³)
3√(p/q) = 44664.59503